Binary oppositions as a means of conceptualizing the artistic picture of the world in the novel “A Place Called Here” by C. Ahern - Сальникова, Екатерина Геннадиевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The author uses a dichotomic method in the analysis of the artistic world of the novel “A Place Called Here” by C. Ahern, considers the implementation of the romantic opposition “Here” – “There” in a contemporary literary text. Particular attention is paid to the antinomy “Lost” – “Found”, which expresses C. Ahern’s message on the structural-compositional, characters representational, semantic and linguistic levels. The article highlights the role of the main character as a mediator between the worlds of “Here” and “There”.